Attitudes of Australian primary school teachers towards the inclusion of students with autism spectrum disorders. Issue 1 (12th June 2018) - Garrad, Traci‐Ann; Rayner, Christopher; Pedersen, Scott
Abstract : Diagnoses of autism spectrum disorder (ASD) have risen dramatically in the last 10 years, with recent estimates at one in every 100 children within Australia. This has resulted in considerable increases in the number of students with ASD entering mainstream education. Teachers' attitudes towards inclusion have been recognised as a key indicator for students' successful inclusion. The main factors posited for determining teachers' attitudes towards the inclusion of students with disabilities, consists of the amount of specialist training received and the length of specific ASD teaching experience. Utilising the Autism Attitude Scale for Teachers for the first time in Australia, we examined 107 primary school teachers' attitudes towards the inclusion of students with ASD within their classrooms. The resulting scores were then analysed to examine the correlations, if any existed, between the amount of specialised training and years of ASD‐specific teaching on teachers' attitude scores. While teachers' attitudes were found to be highly positive, contrary to previous studies, low correlation coefficients were reported between their attitudes and ASD‐specific teaching experience, and their attitudes and the number of ASD‐specific professional development courses they attended. Findings of this study are discussed in the context of the sample population and explore the notion of a sociological and philosophical shift, attributed to the positive promotion efforts of the inclusive education movement, as one possible reason for the divergence in the findings from past research in the field.